Mediação enquanto política pública : a percepção do profissional jurídico - Alves, Mariana Carvalho (2016)
The present study aims to explore and describe lhe perceplion of legal professionals in Rio de Janeiro about the mediation institute. Mediation has lhe enormous potential to contribute to lhe reduction of legal demands by resolving conflicls lhrough negotiation with the presence of an impartial third party. A legal professional can participate in medialion in many ways and his vision regarding the institute is fundamental in order to promote knowledge, awareness and use of this procedure. By analyzing lhe lheoretical foundations of mediation, lhe Brazilian legislation and lhe analysis of data coilected through a questionnaire, lhe position of legal professionals regarding the mediation institute was raised.